Impacts of large-scale forest restoration on socioeconomic status and local livelihoods: what we know and do not know - Adams, Cristina; Rodrigues, Sidney T.; Calmon, Miguel; Kumar, Chetan (Biotropica, 2016)
Forests are sources of wood, non-timber forest products and ecosystems services and goods that benefit society as a whole, and are especially important to rural livelihoods. Forest landscape restoration (FLR) has been proposed as a way to counteract deforestation and reconcile the production of ecosystem services and goods with conservation and development goals. But limited evidence indicates how large-scale forest restoration could contribute to improving local livelihoods. Here, we present a conceptual framework to analyze the effects of large-scale restoration on local livelihoods, and use it to review the scientific literature and reduce this knowledge gap. Most of the literature referred to case studies (89%), largely concentrated in China (49%). The main theme explored was income, followed by livelihoods diversification, off-farm employment opportunities, poverty reduction, equity and the provision of timber and energy as ecosystem services. Nearly 60 percent of the papers discussed the importance of governance systems to socioeconomic outcomes. The reforestation/restoration programs and policies investigated in the studies had mixed socioeconomic effects on local livelihoods depending on other variables, such as availability of off-farm jobs, household characteristics, land productivity, land tenure, and markets for forest products and ecosystem services. We conclude that the effects of large-scale restoration initiatives on local livelihoods may vary due to several factors and is still not clear for many situations; therefore, monitoring over time with clear indicators is needed.